Foreign Communities in Hong Kong, 1840s–1950s - Chu, C. author. aut Link
XIV, 209 p.
Keywords: This collection of essays describes adaptations of minority ethnic groups to cross-cultural situations in Hong Kong from the 1840s through the 1950s. It aims to portray Hong Kong history through the perspectives of foreign communities - the British, Germans, Americans, Indians and Japanese - and to understand how they perceived the economic situation, political administration and culture of the colony.